Aerosol assisted chemical vapor deposition of magnesium orthotitanate (Mg2TiO4) films from a trinuclear molecular precursor. (5th September 2017) - Ehsan, Muhammad Ali; McKee, Vickie; Naeem, Rabia; Hakeem, Abbas Saeed; Mazhar, Muhammad
Graphical abstract: Heterobimetallic complex [Mg2 TiO(TFA)6 (THF)2 (H2 O)] has been designed, structurally characterized and implemented as AACVD precursor for the fabrication of microspherical designed Mg2 TiO4 oxide thin films on FTO glass substrate at 500, 550 and 600 °C. Abstract: Present work demonstrates the synthesis of a novel heterobimetallic complex [Mg2 TiO(TFA)6 (THF)2 (H2 O)] (1 ) (where TFA = trifluoroacetato and THF = tetrahydrofuran), formed from the chemical interaction of magnesium (II) acetate tetrahydrate with titanium (IV) isopropoxide and trifluoroacetic acid in THF solution. Complex (1 ) adequately characterized through attenuated total reflection infrared spectroscopy, single-crystal X-ray diffraction and thermogravimetric analysis was implemented as single source molecular precursor in the aerosol assisted chemical vapor deposition. The deposition of magnesium orthotitanate (Mg2 TiO4 ) ceramic films on fluorine doped tin oxide coated conducting glass substrate was observed at various temperatures of 500, 550 and 600 °C. Film characterization techniques including; X-ray powder diffraction, scanning electron microscopy, energy dispersive X-ray and X-ray photoelectron spectroscopy divulge the fabrication of phase pure spherical shaped Mg2 TiO4 architectures with precise stoichiometry and high purity.